1996
DOI: 10.1136/jmg.33.6.441
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary haemorrhagic telangiectasia with extensive liver involvement is not caused by either HHT1 or HHT2.

Abstract: Hereditary haemorrhagic telangiectasia (HHT) is a genetically heterogeneous dominant disorder. Two disease loci have been mapped to chromosomes 9q3 and 12q. In a large pedigree, with an unusually high number ofpatients with liver vascular malformations, both previously mapped loci have been excluded. The loci for two other inherited vascular malformation diseases, cerebral cavernous malformations and multiple cutaneous and mucosal venous malformations, have also been excluded. Thus we conclude that at least a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 18 publications
2
58
0
3
Order By: Relevance
“…Alternatively, it is also possible that HHT may -at least in some cases -be caused by mutations in a third locus, other than the ALK1 or ENG genes. Evidence for existence of a third HHT locus had been mentioned previously (Piantanida et al, 1996;Wallace and Shovlin 2000). However, in one of these cases (Piantanida et al 1996) an ALK1 mutation was finally detected, after reevaluation, in a large Italian HHT family with liver involvement (Olivieri et al, 2002).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Alternatively, it is also possible that HHT may -at least in some cases -be caused by mutations in a third locus, other than the ALK1 or ENG genes. Evidence for existence of a third HHT locus had been mentioned previously (Piantanida et al, 1996;Wallace and Shovlin 2000). However, in one of these cases (Piantanida et al 1996) an ALK1 mutation was finally detected, after reevaluation, in a large Italian HHT family with liver involvement (Olivieri et al, 2002).…”
Section: Resultsmentioning
confidence: 86%
“…Our results are well in accordance with previous publications on hepatic manifestations in patients with HHT. Although liver involvement was reported for a few patients with ENG mutations, (Berg et al, 2003;Harrison et al, 2003;Cymerman et al, 2003;Shovlin et al, 1997) it was much more often reported for patients carrying mutations in the ALK1 gene (Johnson et al, 1996;Piantanida et al, 1996;Berg et al, 1997;McDonald et al, 2000;Lin et al, 2001;Trembath et al, 2001;Olivieri et al, 2002;Abdalla et al, 2003a & b ;Berg et al, 2003). Liver involvement was not routinely assessed in most of these studies, since the emphasis was mainly on the genotype and not the phenotype, or the reports were on multiple family members and not on unrelated individuals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in the ALK-1 gene in HHT-2 patients include nonsense and missense mutations, as well as insertions and deletions resulting in frameshifts (Johnson et al 1996;Piantanida et al 1996;Olivieri et al 2002).…”
Section: Introductionmentioning
confidence: 99%